The Impact of Body Mass Index on Growth, Schooling, Productivity, and Savings: A Cross-Country Study - Aysit Tansel; Ceyhan Öztürk; Erkan Erdil (Institute of Labor Economics (IZA), 2021)
We examine the relationship between wealth and health through prominent growth indicators and cognitive ability. Cognitive ability is represented by nutritional status. The proxy variable for nutritional status is BMI. We use the reduced form equation in the cubic specification of time preference rate, strongly related to cognitive ability, to estimate this relationship. The growth indicators utilized are GDP per capita, schooling, overall and manufacturing productivities, and savings. We estimate our models using the FE, GMM estimators, and long difference OLS and IV estimation through balanced panel data for the 1980-2009 period. We conclude that the relationship between all prominent growth indicators and BMI is inverse U-shaped. In other words, cognitive ability has a significant potential to progress growth and economic development only in a healthy status.
Keywords: E21; I15; I25; J24; O11; Q18; 330; cognitive ability; time preference rate; BMI; productivity; health; schooling; growth; economic development